SCD rs41290540 single‐nucleotide polymorphism modifies miR‐498 binding and is associated with a decreased risk of coronary artery disease. Issue 3 (21st January 2020) - Liu, Zhou; Yin, Xiaojian; Mai, Hui; Li, Guangning; Lin, Zhijun; Jie, Wanxin; Li, Kanglan; Zhou, Haihong; Wei, Shouchao; Hu, Li; Peng, Wanjuan; Lin, Jiajing; et al.
Abstract: Background: Atherosclerosis is the primary cause of coronary artery disease (CAD), and stearoyl‐CoA desaturase (SCD) is associated with atherosclerosis. However, the associations between variants of SCD and CAD have not yet been decided. Methods: This study analyzed SCD rs41290540 single‐nucleotide polymorphism (SNP) in the 3′‐untranslated region for an association with a risk of CAD among the Chinese Han population. CAD patients and controls were genotyped for SNP rs41290540 in SCD by SNaPshot. The binding affinity of miR‐498 to rs41290540 was determined by a luciferase assay, and SCD expression was assessed using Western blot. Results: A total of 969 CAD patients and 1, 095 control subjects were involved in this study. The SCD rs41290540CC genotype is associated with a decreased risk of CAD compared with the AA genotype. Furthermore, the CC genotype is associated with lower serum total cholesterol (TC). Western blot analysis demonstrated that miR‐498 suppressed the expression of SCD. A luciferase assay confirmed that rs41290540 A>C variation in the SCD 3′UTR inhibits miR‐498 binding. Conclusion: This study demonstrates that the SCD rs41290540 may be associated with a decreased risk of CAD, lower serum TC, and decreased miR‐498 binding. Abstract : We find that the stearoyl‐CoA desaturase rs41290540 may reduce the risk of coronary artery disease. Furthermore, we prove that rs41290540 works by reducing miR‐498 binding.